Rice production in the municipality of São Gabriel, RS (Brazil) - Traversa-Tejero Ignacio Pablo; Bortolotto-Cantarelli Rogério (Journal of the Selva Andina Biosphere, 2020)
Rice is a cereal present in all continents where it is used daily to feed almost half the planet at the time of providing most of the main income of millions of farms. The production of irrigated rice in southern Brazil has peculiar characteristics when compared to other agricultural activities. This research aimed to analyze the production factors of the areas occupied by the rice culture in the municipality of São Gabriel, located in the state of Rio Grande do Sul. The primary data from a statistical database were used. In a complementary way, field questionnaires containing ten variables of the 2017/18 crop were applied. Therefore, the information was tabulated and analyzed using descriptive statistics. It was verified that the rice culture is technified and with high use of inputs. The factors that most influence quality production and high productivity are: differentiated fertilization based on potassium, the use of certified and treated seeds that reduce red rice, the replacement of conventional planting with a more efficient and conservationist one. Productivity levels reach an average value of 8083 kg / ha, which exceeds both the state and national average. The information on the technological packages analyzed in this research refers to the highest productive data in Brazil, therefore, they serve as a guide for agents directly linked to the sector and for formulators of agricultural politics in Brazil. Further research should focus on the study of economic efficiency and cost reduction.